The Bidirectional Relationship Between Sleep and Inflammation Links Traumatic Brain Injury and Alzheimer’s Disease - Green, Tabitha R. F.; Ortiz, J. Bryce; Wonnacott, Sue; Williams, Robert J.; Rowe, Rachel K. (Frontiers in Neuroscience, 2020)
Alzheimer’s disease (AD) and traumatic brain injury (TBI) are diseases during which the fine-tuned autoregulation of the brain is lost. Despite the stark contrast in their causal mechanisms, both AD and TBI are conditions which elicit a neuroinflammatory response that is coupled with physical, cognitive, and affective symptoms. One commonly reported symptom in both AD and TBI patients is disturbed sleep. Sleep is regulated by circadian and homeostatic processes, such that pathological inflammation may disrupt the chemical signaling required to maintain a healthy sleep profile. In this way, immune system activation can influence sleep physiology. Conversely, sleep disturbances can exacerbate symptoms or increase the risk of inflammatory/neurodegenerative diseases. Both AD and TBI are worsened by a chronic pro-inflammatory microenvironment which exacerbates symptoms and worsens clinical outcome. Herein, a positive feedback loop of chronic inflammation and sleep disturbances is initiated. In this review, we discuss the bidirectional relationship between sleep disturbances and inflammation, such that chronic inflammation associated with AD and TBI can lead to sleep disturbances and exacerbated neuropathology. We also highlight the role of microglia and cytokines in sleep disturbances associated with these diseases. The proposed sleep and inflammation-mediated link between TBI and AD presents an opportunity for a multifaceted approach to clinical intervention.